2017
DOI: 10.1371/journal.pone.0178986
|View full text |Cite
|
Sign up to set email alerts
|

The involvement and possible mechanism of pro-inflammatory tumor necrosis factor alpha (TNF-α) in thoracic ossification of the ligamentum flavum

Abstract: Thoracic ossification of the ligamentum flavum (TOLF) is characterized by ectopic bone formation in the ligamentum flavum and is considered to be a leading cause of thoracic spinal canal stenosis and myelopathy. However, the underlying etiology is not well understood. An iTRAQ proteomics was used to reveal the involvement of inflammation factors in TOLF. TNF-α is a pro-inflammatory cytokine implicated in the pathogenesis of many human diseases. Protein profiling analysis showed that the protein level of TNF-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 41 publications
2
60
0
Order By: Relevance
“…Due to the progressive nature of the ossification and the refractoriness to conservative treatment, TOLF generally requires aggressive surgical intervention[14]. Several investigations suggested that potential contributing factors associated with TOLF, such as mechanical effects[57], inflammatory factors [8, 9]and genetic factors[10, 11], but the underlying mechanism of TOLF has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the progressive nature of the ossification and the refractoriness to conservative treatment, TOLF generally requires aggressive surgical intervention[14]. Several investigations suggested that potential contributing factors associated with TOLF, such as mechanical effects[57], inflammatory factors [8, 9]and genetic factors[10, 11], but the underlying mechanism of TOLF has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that inflammatory cytokines promote hypertrophy and ossification of LF cells, but only a number of them (TNF-α, IL-1α and IL-6) have been investigated (1315). The present study predicted that IL10, SOCS3 and ADCY5 may be anti-inflammatory due to their downregulation, while GNG4 may be pro-inflammatory due to its upregulation in OLF.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant BMP2 or BMP14 [also known as growth/differentiation factor (GDF) 5] modification induced the osteoblastic differentiation of LF cells and promoted bone nodule formation, finally triggering neurological impairment in rat models (11,12), while downregulation of Notch2 ameliorated the processes (10). In addition to accelerating osteoblast differentiation via osterix, highly expressed pro-inflammatory cytokines [tumor necrosis factor (TNF)-α, interleukin (IL)-1a and IL-6] appear to stimulate cell proliferation and tissue hypertrophy by upregulating cyclin D1 and c-Myc in OLF (1315). Therefore, targeted regulation of these genes may be potential strategies for the treatment of OLF.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been growing interest in the study of the association between the effect of inflammatory factors and new bone formation. In the previous studies, the involvement of inflammatory factors in TOLF were revealed and have been reported to play an important role in the osteogenesis of ligament flavum cells 11 , 12 . Other investigations also suggested the close correlation between inflammation and oxidative stress in bone formation 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have been conducted on the potential etiology of TOLF at the genetic and cellular levels. While these studies suggested that some potential contributing factors are associated with TOLF, such as mechanical effects 5 - 7 , basic metabolic elements 8 , 9 , degenerative effects 4 , 10 , inflammatory factors 11 , 12 and genetic factors 13 , 14 , the underlying development and progression of TOLF is inadequately understood.…”
Section: Introductionmentioning
confidence: 99%